Bioresorbable Scaffolds: Contemporary Status and Future Directions - Peng, Xiang; Qu, Wenbo; Jia, Ying; Wang, Yani; Yu, Bo; Tian, Jinwei (Frontiers in Cardiovascular Medicine, 2020)
Percutaneous coronary intervention, with its safety, effectiveness and timeliness, has become an important treatment of coronary artery diseases, which has been widely used in clinical practice. But there are still some problems need to be solved urgently. The permanent vessel caging through metallic implants not only prevents the process of positive vessel remodeling and the restoration of vascular physiology, but also makes the revascularization of target vessel more difficult in the future. Bioresorbable scaffolds (BRS) are developed as a potential solution to avoid the above adverse reactions caused by permanent metallic devices. BRS provide temporary support to the vessel wall in the short term, and then gradually degrade over time to restore the natural state of coronary arteries. However, long-term follow-up of large-scale trials raise considerable attentions about the safety of BRS, and the significantly increased risk of late scaffold thrombosis (ScT) limits its clinical application. In this review, we summarize the current status and clinical experiences with BRS to understand application prospects and limitations of these devices. In addition, we focus on the ScT after implantation, as it is the major drawback of BRS at present. We also analyze the causes of ScT and discuss what we can improve to overcome this serious drawback and move the field forward in the future.